2018
DOI: 10.1002/2017sw001776
|View full text |Cite
|
Sign up to set email alerts
|

Midlatitude Plasma Bubbles Over China and Adjacent Areas During a Magnetic Storm on 8 September 2017

Abstract: This paper presents observations of postsunset super plasma bubbles over China and adjacent areas during the second main phase of a storm on 8 September 2017. The signatures of the plasma bubbles can be seen or deduced from (1) deep field‐aligned total electron content depletions embedded in regional ionospheric maps derived from dense Global Navigation Satellite System networks, (2) significant equatorial and midlatitudinal plasma bite‐outs in electron density measurements on board Swarm satellites, and (3) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
125
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(143 citation statements)
references
References 50 publications
16
125
1
1
Order By: Relevance
“…The solar wind and IMF conditions during 7–8 September 2017 have been described in several recent papers (e.g., Aa et al, ; Jin et al, ; Lei et al, ; Li et al, ; Shen et al, ), which are also shown here in Figures a–d. It was a storm with a double main phase.…”
Section: Geomagnetic Conditions Of 7–8 September 2017supporting
confidence: 71%
See 1 more Smart Citation
“…The solar wind and IMF conditions during 7–8 September 2017 have been described in several recent papers (e.g., Aa et al, ; Jin et al, ; Lei et al, ; Li et al, ; Shen et al, ), which are also shown here in Figures a–d. It was a storm with a double main phase.…”
Section: Geomagnetic Conditions Of 7–8 September 2017supporting
confidence: 71%
“…In addition, the substorm‐related shielding electric field could also influence the zonal electric field (Ebihara & Tanaka, ; Jin et al, ). Moreover, several studies have found that under favorable storm time PPEF/PRE conditions, the EPBs can rise to higher altitude with plasma depletion extending along the magnetic field lines to midlatitude regions (e.g., Foster & Rich, ; Kelley et al, ; Ma & Maruyama, ; Mendillo et al, ), while in some extreme cases, the depletion signatures can even be measured around 40° magnetic latitude (MLAT; e.g., Aa et al, ; Cherniak & Zakharenkova, ; Katamzi‐Joseph et al, ; Martinis et al, ). Hence, the storm time morphology of midlatitude ionosphere can be influenced by disturbances initiated from both auroral and equatorial regions.…”
Section: Introductionmentioning
confidence: 99%
“…The nighttime in situ Ne observations of SWA in Figures e–h were consistent with the nighttime topside TEC as shown in Figures e–h, showing localized TEC enhancement, plasma depletions, and bite‐outs between the equator and the midlatitude regions. Aa et al () reported Ne depletions at the equatorial latitudes from SWA and SWC observations during this storm event, which was also observed in our uplooking TEC for GRACE and SWA. The TEC and Ne from SWA were consistent despite the difference in their methods of observation.…”
Section: Observationssupporting
confidence: 88%
“…Therefore, we conclude that the strong eastward IEF penetrated to low‐latitude ionosphere, uplifted the bottomside F layer to higher altitudes and triggered the postsunset FAIs. Aa et al () studied the widely extended plasma bubbles over China during the same storm on 7–8 September 2017 by using data from Global Navigation Satellite System networks. The TEC depletion was observed after 12:45 UT, consistent with the FAIs observed by the HCOPAR.…”
Section: Discussionmentioning
confidence: 99%